Paulus Sebagai Pendidik : Analisis Epistemologi dan Metodologi dalam Surat-suratnya - Yemima Meidina Rista Br Sembiring; Edelwis Pardosi; Agriva J. Pandiangan; Sriwati Sihombing; Hisardo Sitorus (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze Paul as an educator through an epistemological and methodological examination of his letters, as well as an examination of his teaching style within the context of the early church. This research approach is qualitative theological, employing exegetical and hermeneutic analysis of New Testament texts, particularly Paul's letters. This analysis reveals that Paul's educational epistemology is rooted in his encounter with Christ as the source of all truth and spiritual knowledge. According to Paul, knowledge of faith is not the result of human rationality, but rather God's revelation, understood through the work of the Holy Spirit (1 Corinthians 2:10–13). Methodologically, Paul demonstrates a dialogical, argumentative, relational, and transformative teaching approach. He uses logical and communicative rhetoric to guide the congregation in a reflective understanding of the Gospel and emphasizes the importance of living examples as a means of learning faith (1 Corinthians 11:1). Paul also developed a Christocentric and communitarian teaching style, where the church is seen as a living, mutually edifying space for learning about faith, centered on the love of Christ (Colossians 1:28; Ephesians 4:11–16). The results of this study indicate that education, from Paul's perspective, aims for life transformation, not merely the transfer of knowledge. Paul views education as a process of discipleship that produces new life in Christ (Romans 12:2; Galatians 2:20). Thus, Paul's educational model provides theological and practical contributions to contemporary Christian education, placing Christ at the center of epistemology and love as the primary method of teaching.